ENAS Final Formula

0 2 d fxx x0 y0fyy x0 y0 fxy x0 y0 4 f

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: − x0 ) + Fy (x0 , y0, z0 )(y − y0 ) + Fz (x0 , y0, z0 )(z − z0 ) = 0 2 D = fxx (x0 , y0)fyy (x0 , y0 ) − fxy (x0 , y0 ) 4 ∇f (x0 , y0) = λ∇g (x0, y0) g2 (x) b f (x, y )dA = R a h 2 (y ) d f (x, y )dA = R f (x, y ) dy dx g1 (x) f (x, y ) dx dy h 1 (y ) c 1 f (x, y ) dA A R where A is the area of the rectangular region R faverage = β f (r, θ )dA = R ∂r ∂u ∂r ∂u R R ∂r ∂v ∂r ∂v × × ∂r ∂r × ∂u ∂v S= ∂z ∂x f (r, θ ) r dr dθ r 1 (θ ) α n= r 2 (θ ) 2 2 ∂z + ∂y b d dA + 1 dA l f (x, y, z )dV = f (x, y, z )dz dy dx G a c k g2 (x,y ) f (x, y, z )dV = G R f (x, y, z ) dz dA g1 (x,y ) xδ (x, y )dA R δ (x, y )dA x= ¯ R y= ¯ R yδ (x, y )dA R δ (x, y )dA 5 xδ (x, y, z )dV G δ (x, y, z )dV x= ¯ G y= ¯ G z ¯= G yδ (x, y, z )dV G δ (x, y, z )dV zδ (x, y, z )dV G δ (x, y, z )dV θ2 f (r, θ, z )dV = G r 2 (θ ) r 1 (θ ) θ1 g2 (r,θ ) f (r, θ, z ) r dz dr dθ g1 (r,θ ) x = r cos θ, y = r sin θ, z = z f (ρ, θ, φ)...
View Full Document

Ask a homework question - tutors are online